Investigation and Analysis of the Role of Mines in the Economic and Political Development of Afghanistan - Aburagheb Amani; Mohammad Asif Gardezi (Asosiasi Penelitian dan Pengajar Ilmu Sosial Indonesia, 2025)
Afghanistan, often called a